2022
DOI: 10.51972/tfsd.1112388
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Cyberchondria Level and Perceived Stress in Young Adults

Abstract: Purpose: The aim of this study was to investigate the relationship between cyberchondria level and perceived stress in young adults. Material and Methods: This descriptive and relational study was conducted with 547 students studying at a university between September and November 2019. The data of the study were collected through the Personal Information Form, Cyberchondria Severity Scale (CSS), and Perceived Stress Scale (PSS). Results: It was determined that 92.1% of the students were in the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This is supported by the results of Pokharel et al (23). However, it is generally believed that depression in the elderly is influenced by age and marital status (24,25). Research suggests that single individuals between the ages of 70-74 are more likely to experience depression while residing in nursing homes (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is supported by the results of Pokharel et al (23). However, it is generally believed that depression in the elderly is influenced by age and marital status (24,25). Research suggests that single individuals between the ages of 70-74 are more likely to experience depression while residing in nursing homes (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 75%
“…However, it is generally believed that depression in the elderly is influenced by age and marital status (24,25). Research suggests that single individuals between the ages of 70-74 are more likely to experience depression while residing in nursing homes (23)(24)(25)(26)(27). In Türkiye, cultural norms and circumstances may lead elderly individuals, who have lost their spouses, to choose or be required to reside in nursing homes, despite not being a common situation.…”
Section: Discussionmentioning
confidence: 99%
“…The two questionnaires were filled out by 113 young adults, with 74.34% of the male respondents and 25.66% female respondents. The mean age groups Volume 13; Issue: 7; July 2023 To calculate the subscale value of the 12item cyberchondria severity scale to assess the mean value and percentage value, for excessiveness (1,3,6), distress (4, 8, 9), reassurance (5,11,12), and compulsion (2, 7, 10), respectively, the mean value is 2.94 (SD 1.09), 2.89 (SD 1.24), 2.96 (SD 1.16), 2.86 (1.15), and the percentage value is described in chart 3.…”
Section: Resultsmentioning
confidence: 99%
“…4 The study by Lauckner and Hsieh revealed that online binge searches regarding health information could lead to anxiety or depression. 5 Cyberchondria is associated with some unfavorable impacts, such as impaired functioning, poor quality of life, and lower satisfaction with consultations with doctors. 6 In recent years, increase the of maintain the physical fitness with increasing numbers of people engaging to doing exercise as well as yoga.…”
Section: Introductionmentioning
confidence: 99%
“…Young individual between the age range of 18-25 years spent a significant time on the internet and 31.8% of them stated that they always use the internet to search health related issues and show a positive correlation between their perceived stress and cyberchondria (Polat et al, 2022). In addition, a health science study at Ege University about students' health anxiety is documented in the literature.…”
Section: Introductionmentioning
confidence: 99%